Corporate Governance and Dividend Smoothing: Evidence from Pakistani Listed Banks - Ali, Zahid; Hanming, Yang; Ullah, Assad (Asian Journal of Business and Accounting, 2018)
Manuscript type: Research paper Research aims: This paper empirically examines the effects of ownership and board structure on dividend smoothing in Pakistani listed banks between 2006 and 2014. Design/Methodology/Approach: This study employs random Tobit regression to analyse the effects of ownership and board structure on dividend smoothing. It also applies principal component analysis (PCA) to develop a corporate governance index. Research findings: The findings indicate that Pakistani banks with concentrated and foreign ownership, small size audit committee and less independent boards, exhibit higher levels of dividend smoothing. Interestingly, the study finds Pakistani banks having a joint position of CEO and chairperson, demonstrate lesser dividend smoothing. The study concludes that increasing dividends is an alternative monitoring mechanism for shareholders who are enclosed within a weak corporate governance environment such as Pakistan. Theoretical contribution/Originality: This study contributes to previous literature on corporate governance and dividend smoothing by investigating the role of the boards and the ownership structure. It also fills the research gap by investigating the impact of corporate governance on dividend smoothing by using the CG-Index. Practitioner/Policy implications: The findings of this study offer practical implications for payout and corporate governance policies. Higher information asymmetry and regulatory requirements, low shareholders’ rights and weak corporate governance environment make dividend smoothing another tool for safeguarding the interest of minority shareholders in Pakistani listed banks. Currently, regulators in Pakistan are only focusing on corporate governance mechanism as a means of protecting shareholders. This study recommends that smooth dividends can serve as an additional instrument to help safeguard the minority shareholders’ interest from expropriation. Research limitation: The findings of this study may not be generalised due to the small sample size. Keywords: Dividend Smoothing, Corporate Governance, Tobit Regression, Principal Component Analysis, Pakistan JEL Classification: G350, G300, C24, C19